Evidence-Based Psychological Practice for Transgender and Non-Binary Youth: Defining the Need, Framework for Treatment Adaptation, and Future Directions. Issue 3 (2nd July 2020) - Coyne, Claire A.; Poquiz, Jonathan L.; Janssen, Aron; Chen, Diane
ABSTRACT: Mental health disparities between transgender and non-binary (TNB) youth and their cisgender peers are widely documented; however, evidence-based interventions designed to address these disparities do not yet exist. In this article, we outline the mental health needs of TNB youth by identifying relevant treatment targets grounded in developmental and gender minority stress theories and highlight potential gaps in existing evidence-based interventions and initial attempts at adapting evidence-based interventions for TNB youth. We propose different pathways to distinct mental health outcomes in TNB youth based on the intersection of risk and protective factors. Considering the potential for diverse mechanisms driving mental health outcomes in TNB youth, adaptations of evidence-based treatments are necessary to account for gender minority stress processes. We share a case formulation approach that focuses on (1) normalizing the adverse impact of minority stress, (2) facilitating emotional awareness and regulation, (3) restructuring minority stress cognitions, (4) empowering assertive communication, (5) reducing maladaptive avoidance, (6) validating strengths, and (7) building supportive relationships.